AI Companions for Philosophical Health: a Human-in-the-Loop Framework - de Miranda, Luis (Springer Science and Business Media LLC, 2025)
This article explores the reciprocal relationship between artificial intelligence and philosophical health – defined as eudynamic adequation between thoughts and actions. Rather than simply examining how AI might enhance philosophical practice, we investigate how philosophical health can enhance AI applications while preserving the human character of philosophical reflection. We introduce the C.I.P.H.E.R. model (Crealectic Intelligence and Philosophical Health for Eudynamic Realities), a novel framework allowing for AI and human philosophical capacity to collaborate through a “human-in-the-loop” approach. Drawing on original data from a survey of 288 participants conducted between July 2023 and March 2025, we examine contemporary philosophical perspectives across six dimensions: bodily sense, sense of self, belonging, possibility, purpose, and philosophical worldview. Key findings reveal significant patterns including widespread loneliness despite connection (30.6%), evolving self-perception (75.3%), and gaps between purpose recognition and implementation. These empirical insights are evaluated against our theoretical framework for mutual enhancement between philosophical health and AI applications. We address fundamental challenges of technological mediation in philosophical inquiry, particularly regarding embodied understanding and authentic meaning-making.